Influence of assessment services on academic performance among pupils in Kenyan public Primary schools - Omwamba, Janet Mogoi; Raburu, Pamela A.; Aloka, Peter J. O. (Scientific & Academic Publishing, 2016)
Many pupils do not perform well in school despite the concerted efforts to push the course forward. The study investigated the influence of assessment services on academic performance of class eight pupils in public primary school in Kisii South Sub-County Kenya. The researcher used a concurrent triangulation design. Target population was 2670 class eight pupils, 500 class eight teachers, 58 head teachers and 1 QASO. A sample size of 100 class eight teachers and 300 class eight pupils, 10 head teachers and 1 QASO were selected. Quantitative data was analyzed through descriptive statistics while qualitative data was analyzed through thematic framework. Validity was ensured by expert judgment by university lecturers and reliability of the instrument was checked using Cronch bar reliability test, where an index of 0.77413 was obtained. The study found out that that assessment services significantly influenced academic performance of class eight learners. The study recommends that the Ministry of Education should staff primary schools with qualified guidance and counseling personal to dedicate their services to enhance academic achievement. Teacher counselors should provide comprehensive counseling programs to the learners in school to help them enhance academic achievement.
Keywords: Influence; Assessment services; Performance; National examinations; Pupils; Kenyan; Public primary schools